Geometric morphometric analysis of Palatal shape variability after Early neonatal Cheiloplasty - A Systematic Review - Rajagopalan, Anjana; Dash, Bhagabati P; Rana, Shailendra Singh; Pathak, Akhilesh (Journal of Neonatal Surgery, 2025)
Background: Cleft lip and palate (CLP) is a common congenital craniofacial anomalies that pose significant challenges to functional and aesthetic development. Early neonatal cheiloplasty (ENC) aims to restore lip and nasal anatomy promptly, potentially influencing palatal growth and shape variability. Objective: This systematic review assesses palatal shape variability in infants undergoing ENC compared to those receiving late operation protocol (LOP) cheiloplasty, using geometric morphometric analysis. Methods: A systematic search up to April 2025 was conducted across multiple databases following PRISMA guidelines, focusing on studies employing geometric morphometry and principal component analysis to evaluate palatal morphology post-cheiloplasty. The Anatomical Quality Assessment (AQUA) tool was used to evaluate study bias. Results: Four studies met inclusion criteria, showing that palatal shape variability was greatest pre-surgery, especially in bilateral cleft lip and palate (BCLP) patients. Post-ENC, shape variability decreased significantly, approaching non-cleft controls. Inter-canine width remained relatively stable following ENC, with a mild decrease in LOP groups. ENC did not adversely affect anterior or posterior maxillary growth. Both modified Tennison and Veau techniques yielded comparable morphometric outcomes. Conclusion: conducted using 2D methods, which have limitations such as the inability to obtain 3D data and the possibility of measurement errors. 12,13 Our review's contribution will be to integrate 2D and 3D techniques, through geometric morphometric analysis and to study the variations in the palatal shape with and without ENC